Our lives in boxes: perceived community mediators between housing insecurity and health using a PHOTOVOICE approach - Hugo Vásquez-Vera (International Journal for Equity in Health, 2019)
Abstract Background While the negative effects of housing insecurity on health are well known, the mechanisms and mediators of these effects have been less well studied. The aim of this study is to identify perceived mediators involved in the relationship between housing insecurity and health. Methods We used a participatory action research approach, the Photovoice methodology. It promotes a reflective process where participants critically discuss housing insecurity and human health and make recommendations to find solutions for the issues identified. This study was conducted with 18 members of the Platform for People Affected by Mortgages who were living in a situation of housing insecurity in Barcelona during the first half of 2017. Results Participants took 990 photographs, of which 147 were printed for analysis in discussion sessions. 109 of these photographs were then selected for categorization by the participants. 11 major categories emerged, representing various factors related to housing insecurity and health. Most categories were acknowledged as possible mediators of the housing/health problem, including: psychological changes; housing-related material aspects; health-related behaviors; eviction; harassment by financial institutions; and family, neighbors and social network. Others were considered as modifiers that could alter the effects of housing insecurity on health. Co-existing determinants may interact with housing insecurity, thereby increasing negative effects on health. Conclusions Through this participatory approach, the Photovoice project gives insight into the mechanisms underlying the relationship between housing insecurity and human health, and provides valuable recommendations to combat this serious public health issue.